2018
DOI: 10.1039/c8cp02207k
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and accommodation of water clusters by adamantane clusters in helium droplets: interplay between magic number clusters

Abstract: Double magic: 12 adamantane “nanodiamonds” surround, in an icosahedric arrangement, 21 water molecules that form a pentagon dodecahedral structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…24 It was observed that smaller adamantane clusters can also uptake water molecules inside their aggregates, which leads to a subsequent erosion of the parent hydrocarbon cluster. 25 As already mentioned, this experimental observation is expected since water molecules form their own clusters via hydrogen bonds and therefore destroy a much loosely bound LD network that initially hosted them. Note, however, that hydration of the adamantane cluster (n = 13) first results in the replacement of an adamantane moiety with a water molecule conglomerate, (H 2 O) 21 , but manages to preserve the initial structural integrity of the system.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…24 It was observed that smaller adamantane clusters can also uptake water molecules inside their aggregates, which leads to a subsequent erosion of the parent hydrocarbon cluster. 25 As already mentioned, this experimental observation is expected since water molecules form their own clusters via hydrogen bonds and therefore destroy a much loosely bound LD network that initially hosted them. Note, however, that hydration of the adamantane cluster (n = 13) first results in the replacement of an adamantane moiety with a water molecule conglomerate, (H 2 O) 21 , but manages to preserve the initial structural integrity of the system.…”
Section: Resultsmentioning
confidence: 59%
“…Our interest in LD interactions between diamondoids in a 3D environment was partially inspired by recent work of Scheier and coworkers, that offered insight into the aggregation behavior of the smallest diamondoid adamantane in helium nanodroplets. 24,25 Furthermore, the behavior and cluster formation of diamondoids in a 3D environment at extremely low temperatures and pressures is also of interest from the perspective of astrochemistry since recent reports confirmed the presence of diamondoid molecules in space and the HND environment can mimic such interstellar conditions. 26,27 Examples of other hydrocarbons and some other small molecules studied in HNDs exist, 3 e.g., methane, 28,29 ethane, 30 haloalkanes, 31,32 ethylene, 33 benzene, 34 fullerene, [35][36][37][38][39][40][41] alcohols and ethers, 42 methanol, 43 triphenylmethanol, 44 formamide, 45 etc.…”
Section: Introductionmentioning
confidence: 99%
“…The cluster formation of adamantane cations within helium droplets has been explored previously by our group, [49][50][51] employing time-of-flight mass spectrometry. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All rights reserved preferred packing scheme of Ad clusters changes from icosahedral to fcc between n = 19 and 38. The study of Ad was extended with an investigation of HNDs codoped with Ad and water by Kranabetter et al [412]. The authors recorded mass spectra of both pure Ad .…”
Section: Complexes Of Adamantane and Watermentioning
confidence: 99%